Current Account Norms in Natural Resource Rich and Capital Scarce Economies - Araujo, Juliana (IMF Working Papers; Working Paper ;, 2013)
The permanent income hypothesis implies that frictionless open economies with exhaustible natural resources should save abroad most of their resource windfalls and, therefore, feature current account surpluses. Resource-rich developing countries (RRDCs), on the other hand, face substantial development needs and tight external borrowing constraints. By relaxing these constraints and providing a key financing source for public investment in RRDCs, temporary resource revenues might then be associated with current account deficits, or at least low surpluses. This paper develops a neoclassical model with private and public investment and several frictions that capture pervasive features in RRDCs, including absorptive capacity constraints, inefficiencies in investment, and borrowing constraints that can be relaxed when natural resources lower the country risk premium. The model is used to study the role of investment and these frictions in shaping the current account dynamics under windfalls. Since consumption and investment decisions are optimal, the model also serves to provide current account benchmarks (norms). We apply the model to the Economic and Monetary Community of Central Africa and discuss how our results can be used to inform the current account norm analysis pursued at the International Monetary Fund.